Golongan Manusia yang Terhalang dari Hidayah Allah dalam Tafsîr Al-Munîr - Vidianti, Mona Haniza (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This study examines the group of people who are blocked from Allah's guidance, according to Wahbah az-Zuhaili in Tafsir al-Munir. Wahbah intends to name the book of interpretation with the name of the book of Tafsir al-Munir because the book of interpretation can shine on people who study it and read it. The explanation in this tafsir is adapted to the development and needs that occur in today's society. The purpose of this study is to analyze who is included in the group that is blocked from Allah's guidance, according to Tafsir al-Munir. The results of this study also mentioned the character and characteristics of those who are blocked from the guidance of Allah and the consequences for those who are included in the group. The researcher also describes how we can get the guidance of Allah SWT.